Synergistic elucidation of electrochemical oxidation degradation mechanism of PFOA on BDD electrodes: Combining DFT calculations with electrochemical experiments - Zengrong Liu; Yanan Dong; Jingjing Sun; Wanxin Lin; Junfeng Wang (Journal of Environmental Chemical Engineering, 2026)

Long-term outdoor artificial light at night and psychological symptoms among Chinese adolescents: Findings from a national school-based survey - Wenxin Ge; Jun Hong; Liqing Yao; Qiqi Lai; Jingyang Fang; Lixin Hu; Zhengge Jin; Wanxin Wu; Sichun Lin; Yinhuan Guo; Chang Qi; Xiaojian Yin; et al. (Environmental Research, 2026)

Metabolic Modelling Facilitates the Design of Synthetic Communities by Simplifying Natural Microbial Communities - Xinyu Lin; Shifeng Ding; Wanxin Li; Bingang Yang; Yahua Chen; Zhenguo Shen; Jiandong Jiang; Chen Chen; Xihui Xu (Environmental Microbiology, 2026)
Natural microbial communities generally have complex compositions and unclear metabolic interactions, posing constraints on their applications. Clarifying these intricate interactions within microbial communities is challenging for traditional experiment‐based methods. Here, we developed a simulation‐based approach to design synthetic communities (SynComs) by simplifying complex microbial communities through metabolic modelling. We constructed genome‐scale metabolic models (GSMMs) and curated them based on data obtained from straightforward experiments, ensuring these models precisely characterized metabolic features of each strain. By simulations utilizing multi‐strain metabolic models encompassing various strain combinations, we identified helper strains capable of enhancing the degradation efficiency of degrader strains and predicted optimal strain combinations that achieved a simplified community structure while maintaining high pollutant‐degrading efficiency. The simulations also unravelled cross‐feeding of glucosamine, amino acids and organic acids between the degrader and helper strains, which boosted the pollutant‐degrading efficiency of SynComs. Furthermore, helper strains rapidly degraded the toxicant intermediate, thereby alleviating its inhibitory effect on degrader strains. These predictions were further verified experimentally, demonstrating the accuracy and feasibility of metabolic model‐based simulations. Our study establishes a framework for designing simplified SynComs without sacrificing degradation efficiency and highlights the often‐underestimated role of microbial interactions in biodegradation.

Urban heat exposure patterns and domain-specific executive function in adolescents - Lixin Hu; Wenwen Bao; Zhengge Jin; Jun Hong; Wenxin Ge; Yawen Tan; Liqing Yao; Wanxin Wu; Jiaqi Chen; Xiuzhi Yang; Zhuowen Wu; Sichun Lin; et al. (Environmental Research, 2026)

Ultrasensitive electrochemiluminescence aptasensor for heparin-binding protein based on hybridization chain reaction (HCR) amplification and magnetic enrichment - Mengxin Cheng; Wanxin Xu; Yingying Cao; Yue Lin; Shenghang Zhang; Fang Luo; Bin Qiu; Zhenyu Lin (Analytica Chimica Acta, 2026)

Intermittent electrostimulation-modified direct interspecies electron transfer for enhanced methanogenesis in anaerobic digestion of sulfate-rich wastewater - Ye Yuan; Huan Liu; Lulu Zhang; Wanxin Yin; Lin Li; Tianming Chen; Zhaoxia Li; Aijie Wang; Cheng Ding (Bioresource Technology, 2024)

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

A rapid and sensitive time-resolved fluorescence microsphere immunochromatographic test strip for bongkrekic acid detection in edible fungi - Wanxin Lin; Jiadi Sun; Ting Zhang; Jia Xu; Weitao Huang; Xiulan Sun (Food Bioscience, 2024)

Controlling toxic Microcystis blooms: The power of a novel microalgal predator Poteriospumella lacustris in water safety improvement - Shuangshuang Chen; Wanxin Xie; Xu Lin; Hui Zhou; Siqi Teng; Zihan Jiang; Luming Yao; Hong Xu (Journal of Cleaner Production, 2024)

Enhancing effluent quality prediction in wastewater treatment plants through the integration of factor analysis and machine learning - Jiaqiang Lv; Lili Du; Hongyong Lin; Baogui Wang; Wanxin Yin; Yunpeng Song; Jiaji Chen; Jixian Yang; Aijie Wang; Hongcheng Wang (Bioresource Technology, 2024)

RMP-Net: A structural reparameterization and subpixel super-resolution-based marine scene segmentation network - Jiongjiang Chen; Jialin Tang; Shounan Lin; Wanxin Liang; Binghua Su; Jinghui Yan; Dujuan Zhou; Lili Wang; Yunting Lai; Benxi Yang (Frontiers in Marine Science, 2022)
Ocean exploration has always been an important strategic direction for the joint efforts of all mankind. Many countries in the world today are developing their own underwater autonomous explorers to better explore the seabed. Vision, as the core technology of autonomous underwater explorers, has a great impact on the efficiency of exploration. Different from traditional tasks, the lack of ambient light on the seabed makes the visual system more demanding. In addition, the complex terrain on the seabed and various creatures with different shapes and colors also make exploration tasks more difficult. In order to effectively solve the above problems, we combined the traditional models to modify the structure and proposed an algorithm for the super-resolution fusion of enhanced extraction features to perform semantic segmentation of seabed scenes. By using a structurally reparameterized backbone network to better extract target features in complex environments, and using subpixel super-resolution to combine multiscale feature semantic information, we can achieve superior ocean scene segmentation performance. In this study, multiclass segmentation and two-class segmentation tests were performed on the public datasets SUIM and DeepFish, respectively. The test results show that the mIoU and mPA indicators of our proposed method on SUIM reach 84.52% and 92.33%mPA, respectively. The mIoU and mPA on DeepFish reach 95.26% and 97.38%, respectively, and the proposed model achieves SOTA compared with state-of-the-art methods. The proposed model and code are exposed via Github 1 .

Research on gas diffusion of natural gas leakage based on Gaussian plume model - Binbin Wang; Liqiong Chen; Wanxin Lin; Dongrong Wu; Yingchao Fang; Zhao Li (Arabian Journal of Geosciences, 2022)

Using 137Cs and 210Pbex to trace soil erosion rates for a small catchment in the mid-hills of Nepal - Yong Yuan; Donghong Xiong; Han Wu; Lin Liu; Wanxin Li; Chhabi Lal Chidi; Nirmal Mani Dahal; Nilhari Neupane (Journal of Soils and Sediments, 2021)

Spatial variation of soil physical properties and its relationship with plant biomass in degraded slopes in dry-hot valley region of Southwest China - Yong Yuan; Donghong Xiong; Han Wu; Su Zhang; Baojun Zhang; Nirmal Mani Dahal; Lin Liu; Wanxin Li; Wenduo Zhang; Liangtao Shi (Journal of Soils and Sediments, 2020)

Four LysR-type transcriptional regulator family proteins (LTTRs) involved in antibiotic resistance in Aeromonas hydrophila - Yuying Fu; Qilan Cai; Yuqian Wang; Wanxin Li; Jing Yu; Guidi Yang; Wenxiong Lin; Xiangmin Lin (World Journal of Microbiology and Biotechnology, 2019)

Global protein expression profile response of planktonic Aeromonas hydrophila exposed to chlortetracycline - Wanxin Li; Zujie Yao; Xiangyu Zhang; Fang Huang; Wenxiong Lin; Xiangmin Lin (World Journal of Microbiology and Biotechnology, 2017)